A MultiCenter Pilot Randomized Controlled Trial of Remote Ischemic Preconditioning in Major Vascular Surgery. (November 2015) - Healy, D. A.; Boyle, E.; McCartan, D.; Bourke, M.; Medani, M.; Ferguson, J.; Yagoub, H.; Bashar, K.; O'Donnell, M.; Newell, J.; Canning, C.; McMonagle, M.; et al.
A pilot randomized controlled trial that evaluated the effect of remote ischemic preconditioning (RIPC) on clinical outcomes following major vascular surgery was performed. Eligible patients were those scheduled to undergo open abdominal aortic aneurysm repair, endovascular aortic aneurysm repair, carotid endarterectomy, and lower limb revascularization procedures. Patients were randomized to RIPC or to control groups. The primary outcome was a composite clinical end point comprising any of cardiovascular death, myocardial infarction, new-onset arrhythmia, cardiac arrest, congestive cardiac failure, cerebrovascular accident, renal failure requiring renal replacement therapy, mesenteric ischemia, and urgent cardiac revascularization. Secondary outcomes were components of the primary outcome and myocardial injury as assessed by serum troponin values. The primary outcome occurred in 19 (19.2%) of 99 controls and 14 (14.1%) of 99 RIPC group patients ( P = .446). There were no significant differences in secondary outcomes. Our trial generated data that will guide future trials. Further trials are urgently needed.